2017
DOI: 10.1134/s1607672917010082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fatty acid composition revealed differences in the diets of tadpoles of two amphibian species

Abstract: The study of the composition of fatty acid markers of tadpoles of cohabiting amphibian species for the first time revealed differences in their diets: the moor frog Rana arvalis prefers bacteria not associated with plant detritus, whereas the diet of the common spadefoot Pelobates fuscus is based on cyanobacteria, green algae, diatoms, and possibly higher plants. Major differences in the fatty acid composition are determined by the difference in the percentage of eicosapentaenoic and myristic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The large, bell‐shaped secretory area and the pits with bacteria in R. vampyrus are puzzling. Presence of bacteria in tadpole digestive tract can be related to opportunistic environmental colonization, feeding habits, or host–microbe interaction (e.g., Dgebuadze et al, 2017; Lyra et al, 2018). Gut microbiota is known in several tadpoles, and includes numerous phyla of commensal and symbiotic bacteria involved in digestion, development, and immunity (reviewed in Colombo et al, 2015 and Colston & Jackson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The large, bell‐shaped secretory area and the pits with bacteria in R. vampyrus are puzzling. Presence of bacteria in tadpole digestive tract can be related to opportunistic environmental colonization, feeding habits, or host–microbe interaction (e.g., Dgebuadze et al, 2017; Lyra et al, 2018). Gut microbiota is known in several tadpoles, and includes numerous phyla of commensal and symbiotic bacteria involved in digestion, development, and immunity (reviewed in Colombo et al, 2015 and Colston & Jackson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…FAs contain mono-and polyunsaturated essential fats that can only be synthesised by producers before they are assimilated by consumers. A separate study analysing FAs suggests that bacteria associated with detritus or sediments can be important food resources that are assimilated by tadpoles (Dgebuadze et al, 2017). FA analyses are often expensive and require more sample preparation time than stable isotope analysis (Altig et al, 2007), but the examination of FA profiles in food-web components has a notable advantage over stable isotopes because consumers with selective feeding habits may exhibit different FA profiles that cannot easily be resolved by stable isotope analyses alone (Lau, Leung, & Dudgeon, 2008).…”
Section: Fatty Acid Analysesmentioning
confidence: 99%
“…As consumers typically assimilate large quantities of FAs from their animal prey, FAs can be used as tracers to quantify trophic transfers (Napolitano, 1999). Dgebuadze et al (2017) found that bacteria associated with plant detritus contributed to the FA composition of Rana arvalis, whereas the FA profiles of Pelobates fuscus indicated that cyanobacteria, green algae, diatoms, and possibly higher plants were more important diet components. used FAs to examine trophic relationships of three common tadpole species (Pseudacris crucifer, L. clamitans, and F I G U R E 4 Mean trophic position (± standard deviation) of tadpole species along a gradient of pond permanency (semipermanent, permanent, and temporary) in Neotropical (a) and Nearctic (b) regions.…”
Section: Fatty Acid Analysesmentioning
confidence: 99%
See 2 more Smart Citations